2019
DOI: 10.1093/rheumatology/kez409
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of comorbidity indices and lung diseases in early rheumatoid arthritis: a UK population-based study

Abstract: Objectives We assessed comorbidity burden in people with RA at diagnosis and early disease (3 years) and its association with early mortality and joint destruction. The association between lung disease and mortality in RA is not well studied; we also explored this relationship. Methods From a contemporary UK-based population (n = 1, 475 762) we identified a cohort with incident RA (n = 6591). The prevalence of comorbidities a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 38 publications
1
34
0
4
Order By: Relevance
“…On the other hand, that female sex and baseline age ≥ 49 years are positively associated with the increased HRs of rheumatic disorders is consistent with the fact that female sex and old age had been identi ed as risk factors for RA [39]. CCI score ≥ 1 and baseline COPD were associated with increased HRs of rheumatic disorders coincides that comorbidities including respiratory disease were more common in patients with RA at diagnosis than controls [40]. Patients with rheumatic disorders have increased prevalence of metabolic syndrome including dylipidemia [41] and acute myocardial infarction risk increased by 38% [42] in RA patients might explained why dyslipidemia were associated with increased HR of rheumatic diseases.…”
Section: Discussionsupporting
confidence: 76%
“…On the other hand, that female sex and baseline age ≥ 49 years are positively associated with the increased HRs of rheumatic disorders is consistent with the fact that female sex and old age had been identi ed as risk factors for RA [39]. CCI score ≥ 1 and baseline COPD were associated with increased HRs of rheumatic disorders coincides that comorbidities including respiratory disease were more common in patients with RA at diagnosis than controls [40]. Patients with rheumatic disorders have increased prevalence of metabolic syndrome including dylipidemia [41] and acute myocardial infarction risk increased by 38% [42] in RA patients might explained why dyslipidemia were associated with increased HR of rheumatic diseases.…”
Section: Discussionsupporting
confidence: 76%
“…Being able to diagnose the presence of an ILD at an early stage, through repeatable and non-invasive methods, should be a prerogative of the rheumatologist dealing with RA patients. The recognition of comorbidities, and in particular pulmonary conditions, has been shown to be a fundamental element for prognostic purposes already in the early stages of the disease [16]. The mean time between RA-ILD diagnosis and RA diagnosis is 4.9 years, and at RA-ILD diagnosis a significant reduction in DLco is already present, with oxygen-therapy needed in half of the subjects [17].…”
Section: Discussionmentioning
confidence: 99%
“…Several recent epidemiologic studies have also identified significant increases in the prevalence of lung disease, particularly AD, during pre‐RA, supporting lung disease as a risk factor for developing RA . Specifically, Zaccardelli et al found that a clinical diagnosis of asthma was present in 18% of serum ACPA + subjects who later developed classified RA compared to only 6% in matched controls.…”
Section: The Lung In Pre‐ramentioning
confidence: 98%
“…Notably, many of these studies have used imaging findings and/or pulmonary function testing (PFTs) to identify AD in RA. In contrast, a clinical diagnosis of AD, in particular obstructive lung disease, is often less prevalent, although still significantly higher in RA patients compared to controls . For example, in a meta‐analyses of approximately 32 000 RA patients and approximately 122 000 controls, there was a twofold risk of COPD in individuals with RA compared to controls .…”
Section: Lung Involvement In Established Ramentioning
confidence: 98%